2017
DOI: 10.2298/vsp150831191v
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors in premature infants with retinopathy of prematurity after anti-vascular endothelial growth factor (anti-VEGF) therapy

Abstract: Background/Aim. Retinopathy of prematurity (ROP) is a vasoproliferative retinopathy which affects the blood vessels of the retina during its development. The aim of this study was to evaluate the incidence and the degree of refractive errors in premature infants with severe ROP treated with anti-vascular endothelial growth factor (anti-VEGF) (bevacizumab). Methods. This prospective study included 21 patients (42 eyes) nine months old who received intravitreal injection of anti-VEGF therapy. The control group c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Two articles 23 25 reported the LT, which did not differ significantly between the anti-VEGF drug and laser groups (MD=0.06 mm; 95% CI −0.56 to 0.67, p=0.85), and I 2 was 97% ( online supplemental material : S4 forest plot).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles 23 25 reported the LT, which did not differ significantly between the anti-VEGF drug and laser groups (MD=0.06 mm; 95% CI −0.56 to 0.67, p=0.85), and I 2 was 97% ( online supplemental material : S4 forest plot).…”
Section: Resultsmentioning
confidence: 99%
“…Three articles 23 25 26 reported the AL, with 251 eyes in the anti-VEGF drug group and 362 eyes in the control group ( figure 4 ). There was no significant difference in the AL between the groups (MD=−0.04 mm, 95% CI −0.30 to 0.21), and the heterogeneity was low (I 2 =30%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nine papers, including 1046 eyes of 547 premature infants treated for ROP, reported similar refractive outcomes between the two treatment modalities (Table 1). In a study by Vujanovic et al [30], refractive astigmatism and high myopia were more common in the laser-treated eyes, and anisometropia was significantly greater than that in the anti-VEGF-treated eyes. Therefore, this study was included in the first category.…”
Section: Resultsmentioning
confidence: 91%
“…Some studies revealed comparable refractive outcomes between the two treatment modalities for ROP [9,16,23,30,[44][45][46][47][48]. The treatment type did not influence long-term refractive outcomes in ROP [44].…”
Section: Discussionmentioning
confidence: 99%